KUALITAS KELEMBAGAAN UPTD PPA KABUPATEN BANTUL DALAM USAHA PENANGANAN KASUS SERTA PERLINDUNGAN PEREMPUAN DAN ANAK - Safa Arub Nadia; Safira Zata Yumni (Jurnal Riset Daerah, 2023)
Unit Pelaksana Teknis Daerah Perlindungan Perempuan dan Anak (UPTD PPA) Bantul Regency as a public service institution has an important role in providing case handling services, assistance and protection for women and children who experience violence, discrimination and other problems. This research aims to determine the institutional quality of UPTD PPA Bantul Regency which influences service performance as well as factors that support and detain service implementation. This research uses a qualitative-descriptive method. The data collection process was carried out by interviews, observation and documentation. Data processing was carried out by triangulation and analyzed in the form of descriptive descriptions containing descriptions of every institutional aspect in the UPTD PPA Bantul Regency. Based on the research results, proven that the institutional quality of the UPTD PPA Bantul Regency has met standards in the aspects of consultation and complaint mechanisms, service policies, quality of human resources, as well as networks and information systems. However, services at UPTD PPA still have problems in performing assessments due to a lack of clinical psychologists, low levels of security due to a lack of security officers, and incomplete infrastructure in safe houses. Therefore, it is necessary to add clinical psychologists, security personnel, and complete infrastructure in safe houses to increase service capacity.